Phytochemical constituent, α-amylase and α-glucosidase inhibitory activities of Black Soybean (Glycine soja (L.) Merr.) ethanol extract - Sutjiatmo, Afifah Bambang; Narvikasari, Suci; Solihat, Ananda Khairunisa; Widowati, Wahyu; Kusuma, Hanna Sari Widya; Zahiroh, Fadhilah Haifa (Pharmaciana, 2024)
Diabetes is characterized as a hyperglycemic condition impacted by β-cell dysfunction and insulin deficiency. Black soybean (Glycine soja (L.) Merr.) is widely known as an origin of nutritious food that has shown activities in preventing cardiovascular disease and reducing hyperglycemia. This research aimed to evaluate the potential of black soybeans ethanol extract (BSEE) as an α-amylase and α-glucosidase activity inhibitor. Black soybean seeds were extracted using the Soxhlet method with 50% ethanol as a solvent. The extract Soybean seeds were screened for the presence of phytochemicals. Inhibitory activity of α-amylase and α-glucosidase enzymes was tested in vitro with acarbose as a control. The absorbance measurement was conducted at 565 nm and 400 nm, respectively. BSEE contained alkaloids, flavonoids, polyphenols, saponins, quinones, tannins, and terpenoids. The results indicated that BSEE exhibited a weak inhibitory effect of α-amylase enzyme activity, with an IC50 value of 360.37 ± 20.80 µg/ml, in contrast to acarbose, which showed a significantly lower IC50 of 4.02 ± 0.56 µg/ml. Meanwhile, BSEE was classified as an active inhibitor of α-glucosidase enzyme activity, presenting 25.67 ± 0.27 µg/mL IC50 value, while acarbose demonstrated 10.85 ± 0.5 µg/mL IC50 value. In conclusion, BSEE inhibits α-amylase and α-glucosidase.